PERSEPSI MAHASISWA TERHADAP PENGGUNAAN APLIKASI SYAM-OK - Siti Nur Fadillaturrisqui; Usman Usman (Universitas Negeri Makassar, 2022)
Student Perceptions of the Use of the SYAM-OK Application. The purpose of this study was to describe the perceptions of students of the Indonesian Language and Literature Education study program towards the use of the SYAM-OK application. This research is quantitative descriptive. The method used in this study is a survey method with data collection techniques using a questionnaire. Research data obtained from respondents' answers via Google Form. The results of the accumulation state that in terms of perceived ease of use, respondents' answers are in the